Discouraged Immigrants and the Missing Pop in EPOP - Peter Norlander; Todd A. Sorensen (Institute for the Study of Labor (IZA), 2016)
We address the impact of declining migration on the measurement of labor market health. We first document an historically significant decline in the growth rate of the U.S. foreign born population since 2000. A decomposition shows that nearly two-thirds of the decline can be attributed to declining pull factors in the U.S. Had this decline not occurred, there would have been approximately 7.2 million more immigrants present in the U.S. in 2013. Making a conservative assumption about the hypothetical likelihood of employment for these "Discouraged Immigrants," a recalculation of the Employment to Population Ratio reveals a 13% larger decline since 2000 than is shown when conventionally measured.
Keywords: J21; J61; 330; employment data; population; international migration